2019
DOI: 10.1007/s10899-019-09899-0
|View full text |Cite
|
Sign up to set email alerts
|

The Winners and the Losers: Tax Incidence of Gambling in Finland

Abstract: Gambling markets have grown rapidly for the last few decades. As a result, gambling is also a very important and common source of tax income for many governments these days. This raises a question about the overall fairness of the gambling taxation systems. In this paper, we aim to study the tax incidence of gambling in Finland. First, we analyse who are the expected payers of the gambling taxes and second, who are expected to be the receivers of the gambling-tax based contributions. In the first part of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 27 publications
(72 reference statements)
2
9
0
Order By: Relevance
“…Overall, respondents in the low GE group differed from those in the intermediate and high GE groups. Those in the highest or intermediate GE group were more likely to be male which is in accordance with earlier studies (McCormack et al, 2014;Roukka & Salonen 2020;. This may be related to the nature of the games men favour.…”
Section: Discussionsupporting
confidence: 91%
“…Overall, respondents in the low GE group differed from those in the intermediate and high GE groups. Those in the highest or intermediate GE group were more likely to be male which is in accordance with earlier studies (McCormack et al, 2014;Roukka & Salonen 2020;. This may be related to the nature of the games men favour.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, gambling revenues are properly referred to as a regressive tax. 7 , 13 Further, we found that almost a third of those experiencing problem or at-risk gambling are receiving at least one form of social security benefit, there is a big chance that social security benefits are used to gambling. As amount of social security benefits is small, money spent on gambling is away from essential expenses of everyday life.…”
Section: Discussionmentioning
confidence: 81%
“…Gambling expenditure tends to increase with income, 5 but people with lower incomes spend relatively larger proportion of their total budget on gambling. 6 , 7 However, there are also studies that have shown higher absolute gambling expenditure among lower income groups on some forms and in some localities. 8 Similarly, problem gambling has been linked with lower personal and household income, 9 perhaps due to less capacity to absorb gambling losses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Finnish Lotteries Act (23.11.2001/1047, updated 21.12.2016/1286) states that a gambling monopoly is justifiable to prevent and reduce gambling-related harm, but such legal justification does not appear to be in line with the economic realities of raising profit for society. The proceeds from gambling in Finland do not necessarily benefit the geographical areas from which they are collected ( Roukka & Salonen, 2019 ). Moreover, Finnish EGMs are disproportionally placed in poor neighbourhoods ( Raisamo et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%